X-Linked Dilated Cardiomyopathy: A Cardiospecific Phenotype of Dystrophinopathy - Akinori Nakamura (MDPI AG, 2015)
X-linked dilated cardiomyopathy (XLDCM) is a distinct phenotype of dystrophinopathy characterized by preferential cardiac involvement without any overt skeletal myopathy. XLDCM is caused by mutations of the Duchenne muscular dystrophy (DMD) gene and results in lethal heart failure in individuals between 10 and 20 years. Patients with Becker muscular dystrophy, an allelic disorder, have a milder phenotype of skeletal muscle involvement compared to Duchenne muscular dystrophy (DMD) and sometimes present with dilated cardiomyopathy. The precise relationship between mutations in the DMD gene and cardiomyopathy remain unclear. However, some hypothetical mechanisms are being considered to be associated with the presence of some several dystrophin isoforms, certain reported mutations, and an unknown dystrophin-related pathophysiological mechanism. Recent therapy for Duchenne muscular dystrophy, the severe dystrophinopathy phenotype, appears promising, but the presence of XLDCM highlights the importance of focusing on cardiomyopathy while elucidating the pathomechanism and developing treatment.